Spectrum of Resting 12-Lead Electrocardiographic Findings in Peri- Partum Cardiomyopathy: Report of 100 Consecutive Patients - Umar, Hayatu; Bamaiyi, Adamu Jibril (Cardiology and Cardiovascular Medicine, 2020)
Electrocardiography (ECG) is an investigative procedure in PPCM screening and monitoring. Although ECG features among PPCM patients have been shown to vary among different ethnicities, this has not been fully described among the Hausa/Fulani ethnicity. In the present study therefore, we described the ECG features of PPCM among Hausa/Fulani ethnic group of Nigeria and we relate same with left ventricular (LV) functions and dimensions. One hundred women who fulfilled the diagnostic criteria for PPCM were evaluated. A standard resting 12-lead ECG and echocardiographic examination were performed on the patients. Data analysis was done using IBM SPSS statistical software (version 22). Mean age of the patients was 27.11 ± 7.83 years and were 98% of the Hausa/Fulani ethnicity. The heart rate (HR) was fast (117.54 ±15.02). Most patients had abnormal ST and T-waves (70% and 83%, respectively). The mean QTc index was 460.97 ±40.69, with 47% of them having prolonged QTc. However, the mean QRS interval was within normal (89.89 ±20.00ms). Although, ejection fraction (EF) showed a significant inverse relationship with the left ventricular internal diameter in diastole (LVIDd) (r = - 0.234, p = 0.021, β-coefficient =-0.013, R2 =0.027), neither of the EF nor the LVIDd showed significant relations with the indices of QRS voltage amplitudes, even though about 82% of the patients had LV dilatation. We conclude that ECG abnormalities are rife among PPCM patients of Hausa/Fulani extraction of Nigeria and may be used alongside other standard protocols to screen and monitor treatment of the patients in this region.